Electrochemical performance of Na0.6[Li0.2Ni0.2Mn0.6]O2 cathodes with high-working average voltage for Na-ion batteries. Issue 12 (6th March 2017) - de la Llave, Ezequiel; Nayak, Prasant Kumar; Levi, Elena; Penki, Tirupathi Rao; Bublil, Shaul; Hartmann, Pascal; Chesneau, Frederick-Francois; Greenstein, Miri; Nazar, Linda F.; Aurbach, Doron
Abstract : Lithium doping improves structural stability and increases average working potential of manganese oxide cathodes for sodium-ion batteries. Abstract : Na0.6 [Li0.2 Ni0.2 Mn0.6 ]O2 is synthesized by a self-combustion reaction (SCR) and studied for the first time as a cathode material for Na-ion batteries. The Na0.6 [Li0.2 Ni0.2 Mn0.6 ]O2 cathode presents remarkable high rate capability and prolonged stability under galvanostatic cycling. A detailed analysis of X-ray diffraction (XRD) patterns at various states of cycling reveals that the excellent structural stability is due to a primarily solid-solution sodiation/desodiation mechanism of the material during cycling. Moreover, a meaningful comparison with Na0.6 MnO2 and Na0.6 [Li0.2 Mn0.8 ]O2 reveals that the Na0.6 [Li0.2 Ni0.2 Mn0.6 ]O2 cathode achieves a very high working-average voltage that outperforms most of the lithium-doped manganese-oxide cathodes published to date.